2022
DOI: 10.1126/science.abn6358
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and ecological footprint of Global Ocean RNA viruses

Abstract: DNA viruses are increasingly recognized as influencing marine microbes and microbe-mediated biogeochemical cycling. However, little is known about global marine RNA virus diversity, ecology, and ecosystem roles. In this study, we uncover patterns and predictors of marine RNA virus community- and “species”-level diversity and contextualize their ecological impacts from pole to pole. Our analyses revealed four ecological zones, latitudinal and depth diversity patterns, and environmental correlates for RNA viruse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 122 publications
3
56
0
Order By: Relevance
“…Hence, the host prediction of RNA viruses is still at an exploratory stage. Based on abundance co-occurrence suggested by Dominguez-Huerta et al 37 , almost half of the virus-host interactions observed in this study occurred in August of both two years, and all of them were positively correlated (Fig. 5).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Hence, the host prediction of RNA viruses is still at an exploratory stage. Based on abundance co-occurrence suggested by Dominguez-Huerta et al 37 , almost half of the virus-host interactions observed in this study occurred in August of both two years, and all of them were positively correlated (Fig. 5).…”
Section: Discussionsupporting
confidence: 62%
“…Very recently, the importance of the marine RNA virosphere, identi ed by rapid advances in metagenomic and metatranscriptomic analyses, was revealed in a series of key papers 5,6,15−19 . A total of 44,779 RNA viral contigs, identi ed in the ~ 28 terabases (Tb) of Global Ocean RNA sequences, revealed ve new phyla "Taraviricota", "Pomiviricota", "Arctiviricota", "Paraxenoviricota", and "Wamoviricota", and four RNA viral ecological zones 19,20 . However, there remains a lack of research on the spatiotemporal dynamics and community structure changes of RNA viruses and their relationships with hosts, which is critical to the understanding of their activity and ecological roles in the sea.…”
Section: Introductionmentioning
confidence: 99%
“…The application of high-throughput sequencing technology for virus hunting has greatly promoted the development of virology in recent years that accelerated the discovery of virus diversity, origin and evolution from various materials including animals, plants, fungi and environment ( Adams et al, 2009 ; Roossinck et al., 2015 ; Marzano et al., 2016 ; Shi et al., 2016 ; Chiapello et al., 2020 ; Myers et al., 2020 ; Wang et al., 2021 ; Ruiz-Padilla et al., 2021 ; Kondo et al., 2022 ; Dominguez-Huerta et al., 2022 ). For mycoviruses, many studies have reported that the co-infection of a large number of viruses in single fungal strains is a common phenomenon, which usually appeared in the necrotrophic fungi R. solani and S. sclerotiorum ( Bartholomäus et al., 2016 ; Mu et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Microbes are the main drivers of the biogeochemical cycles that define ecosystems, but they also are susceptible to virus infection, e.g., it is estimated that ∼20% of the bacteria in the oceans are lysed by viruses per day ( Suttle, 1994 ). These ongoing viral infections shape microbial community structures and are necessary for nutrient cycling ( Dominguez-Huerta et al, 2022 ).…”
Section: Viruses At the Planetary Scale: The Virospherementioning
confidence: 99%